The cost‐effectiveness of genotyping versus sequencing for prenatal cystic fibrosis carrier screening. (12th August 2021) - Avram, Carmen M.; Dyer, Alexandria L.; Shaffer, Brian L.; Caughey, Aaron B.
Abstract: Objective: We investigated the cost‐effectiveness of three sequential prenatal cystic fibrosis (CF) carrier screening strategies: genotyping both partners, genotyping one partner then sequencing the second, and sequencing both partners. Method: A decision‐analytic model compared the strategies in a theoretical cohort of four million pregnant couples in the US population and five racial/ethnic sub‐populations. Inputs were obtained from literature and varied in sensitivity analysis. Outcomes included cost per quality‐adjusted life year (QALY), missed carrier couples, affected newborns, missed prenatal diagnoses, terminations, and procedure‐related losses. The cost‐effectiveness threshold was 100, 000/QALY. Results: Sequencing both partners identified 1099 carrier couples that were missed by genotyping both partners, leading to 273 fewer missed prenatal diagnoses, 152 more terminations, and 152 fewer affected newborns. A similar trend was observed in the genotyping followed by sequencing strategy. The incremental cost‐effectiveness ratio of genotyping followed by sequencing compared to genotyping both partners was 180, 004/QALY and the incremental cost‐effectiveness ratio of sequencing both partners compared to genotyping followed by sequencing was 17.6 million/QALY. Sequencing both partners was cost‐effective below 339 per test, genotyping/sequencing between 340 and 1837, and genotyping both partners above 1838. Sequencing was not cost‐effective among five racial/ethnic sub‐populations. Conclusion: Despite improved outcomes, sequencing for prenatal CF carrier screening was not cost‐effective compared to genotyping. The clinical significance of the incremental cost‐effectiveness of CF carrier screening is a matter of deliberation for public policy debate. Key points: What is already known about this topic? Next‐generation sequencing for prenatal cystic fibrosis (CF) carrier screening may better detect carrier couples across diverse race/ethnicities compared to the recommended 23‐pathogenic‐variant panel What does this study add? Among all populations, sequencing both partners had the highest effectiveness with the fewest missed carrier couples, missed prenatal diagnoses, and newborns with CF. Sequencing as a first‐line approach was more costly for prenatal CF carrier screening, despite improved carrier detection and outcomes. However, the worth and clinical significance of CF carrier screening is a matter for public policy debate